Supply vs. Demand of Agri-industrial Meat and Fish Products: A Chicken and Egg Paradigm? - G. Rivera-Ferre, Marta (The International Journal of Sociology of Agriculture and Food, 2009)
In this essay, I explore the driving forces behind the worldwide increase of meat and fish consumption. Emphasis is put on defining whether this increase is mainly a demand-driven or a supply-driven process. An increasing demand at the consumer side has been presented as an illustration of the power of consumers to determine the trends in food production. At the same time, this argument is used to justify efforts in increasing production and productivity through the intensification of animal and aquaculture production systems. This view has apparently convinced governments and development organizations, which provide funds and an appropriate legal environment to promote these production systems. I argue, however, that increased levels of demand are rather a supply-driven process resulting from a combination of supply increments and cost externalization, which afterwards have effects on both product prices and consumer habits. But supply-driven increased consumption may cause health, environmental and social problems, and ends up with the disempowerment of both producers and consumers. Since the power and freedom of choice attributed to consumers are questionable and changes in demand may be an effect of supply itself, they cannot be used to justify the intensification of animal husbandry and aquaculture.